Endovascular Treatment of Complex Intracranial Aneurysms With LEO+ Stents: The LEO II Cohort Study - Eker, Omer F.; Levrier, Olivier; Houdart, Emmanuel; Bonja, Marianne; Herbreteau, Denis; Bonafé, Alain; Desal, Hubert; , the LEO+ II Investigators (Frontiers in Neurology, 2022)
Introduction: Stent-assisted coiling is an established treatment option for intracranial aneurysms, particularly wide neck aneurysms with complex anatomy. The purpose of the present study was to assess the safety and efficacy of LEO+ stents in the treatment of intracranial aneurysms. Materials and Methods: A prospective, observational, multicenter study including 12 centers was performed on patients with ruptured, unruptured and recanalized intracranial aneurysms treated with LEO+ stents. The primary efficacy endpoint was the rate of complete aneurysmal occlusion at 18 months post-procedure, and the primary safety endpoint was the morbidity and mortality at 18 months post-procedure. Results: From March 2015 to June 2017, 176 patients were enrolled (mean age of 54.8±11.5 years; 65.9% women). The aneurysms were located mainly in the anterior communicating artery (29.2%) and the middle cerebral artery (28.6%). They were mostly saccular (94%), with a mean dome size of 5.3±2.6 mm and a mean aspect ratio of 1.2±1.0. Three percent of the aneurysms were treated in the acute phase of rupture. Complete/nearly complete aneurysmal occlusion and major recanalization were observed in 89% (n=146/164) and 1.8% (n=3/164) of patients at 18-month follow-up, respectively. The LEO+ related mortality rate was 0.6% (n=1/170), the morbidity rate was 4.1% (n=7/170) and these patients were mRS 0-2 at 18 months. Conclusion: Our results reflecting the use of LEO+ stents in real world conditions confirm the efficacy and safety of LEO+ stents in the management of complex intracranial aneurysms.